World Music : A Very Short introduction - Bohlman, Philip V., 1952- (Karachi Oxford University Press, 2002)
"Philip Bohlman asks: What is music? If the question is simple, the answers are not. In this fascinating introduction to the remarkable diversity of world music - from Swiss yodeling to pilgrims' chants, Yiddish folk songs to Àrt-Song' from Tunis - Bohlman explores the interpretation and, sometimes, misinterpretation of world music by the West."--Jacket.
Include Index
Keywords: World Music--Analysis, Appreciation -- World Music